'La justice est pleine de charité', ou la 'révélation' d'Émile Durkheim vue par Gaston Richard. Issue 1 (1st December 2022) - Rol, Cécile
Abstract: Gaston Richard was not only among the first to be informed of the 'revelation' that Durkheim announced about his reading of William Robertson Smith in 1895. Among all the Durkheimians, Richard was alone in publicly declaring himself on the matter. The radical nature of his witness went far beyond the fact of calling into question the date as well as the subject of this 'revelation'. For Richard, the constitution of Durkheim's religious sociology was ultimately 'only a moment from a more ample study' about obligation. The originality of his analysis derives as much from the fact of having seen the main source of Durkheim's inspiration in the neo-criticism of Charles Renouvier (parts 1 and 2) as from having criticized Durkheim's state-sociology, which was, if not the conclusion, then at least its political translation (part 3). Résumé: Gaston Richard ne fut pas seulement aux toutes premières loges de la 'révélation' dont Durkheim fit part au sujet de sa lecture de William Robertson Smith, en 1895. De tous les durkheimiens, il fut encore le seul à s'y prononcer publiquement. La radicalité de son témoignage ira bien au-delà du fait de remettre en cause la date tout autant que l'objet de cette 'révélation' : pour Richard, la constitution de la sociologie religieuse durkheimienne ne fut en définitive 'rien qu'un moment d'une étude beaucoup plus ample' sur l'obligation. L'originalité de son analyse tient autant au fait d'en avoir vu la source d'inspiration majeure dans le néo-criticisme de Charles Renouvier (parties 1 & 2) que dans celui d'avoir critiqué la sociologie durkheimienne de l'État, qui en était sinon la conclusion, du moins la traduction politique (partie 3).